Influence of the interannual variability of the Kuroshio Extension on the Mediterranean trough in the cold season - Jiang, Yuxi; Sun, Jianxiang; Ma, Li; Li, Huan; Wang, Yanshuo (Frontiers in Marine Science, 2022)
The impacts of the Kuroshio Extension (KE) interannual fluctuation on the Mediterranean trough (MedT) and associated Euro-Mediterranean climate in wintertime are analyzed in this study. It appears that when the KE index is positive (corresponds to a stable KE state with sharp sea surface temperature front and subsided oceanic eddies), the MedT is observed to be stronger in the west of its climatological position, resulting in a colder condition to the west of the Black Sea and more precipitation in the East Mediterranean and Anatolia Plateau. The opposite atmospheric pattern holds when the KE index is negative (unstable KE state). The empirical orthogonal function analysis is performed on 500-hPa geopotential height to obtain the dominant modes of MedT. The results show the KE index is significantly correlated with the intensity and zonal displacement of MedT, with correlation coefficients of 0.57 and 0.40, respectively. The low-frequency Rossby wave activity and high-frequency eddies are revealed as the prominent contributors to this co-variability between the KE and MedT. The upward turbulent heat flux transport from the ocean to the atmosphere strengthened by the stable KE activates the Rossby waves propagating upward and westward to the MedT region, contributing to approximately 30% of the MedT deepening. Meanwhile, the KE-driven Rossby waves intensify the background baroclinicity to the north of the Mediterranean Sea and thus enhance the transient eddy activity, consequently leading to another 20% of the MedT amplification via the eddy–mean flow interaction. The findings highlight the impacts of the KE state on the meteorological conditions in the Euro-Mediterranean region, which can potentially optimize the forecast accuracies of the MedT and associated Euro-Mediterranean climate variability.